Teaching Factory Management at Vocational High School Center of Excellence in Temanggung Regency - Hastuti, Erni; Murniati, Ngurah Ayu Nyoman; Sudana, I Made (Universitas Muhammadiyah Ponorogo, 2025)
The research aims to analyze and describe the management of the Teaching Factory at the Center of Excellence Vocational School, especially in Temanggung Regency. The research was conducted at State Vocational High School 2 Temanggung, Central Java, focusing on planning, organizing, actuating, and controlling.Â This qualitative descriptive study employed observation, interviews, and documentation with subjects including the school principal, deputy head of curriculum, teaching factory manager, head of skills concentration, and vocational teachers. Data were validated using triangulation techniques and analyzed using the Miles and Huberman model. Findings revealed that: 1) Planning involved a strategic partnership with theÂ industry through the Link and Match 8+i strategy, product determination based on competency achievement and market interest, development of learning tools with industry, preparation of competent teachers, environmental arrangement and facilities according to industry standards, governance as an independent business;2) Organizing involved preparation of an organizational structure integrated into the school organizational structure, division of tasks through the Teacher Task Distribution Decree; 3) Execution involved utilized block schedules, real project-based products, delivery of products after passing quality control, after-sales service; 4) Control involved management, practice settings and industrial culture, integrated learning, marketing/promotion through direct and digital marketing, quality, continuity product and innovation, continuous HR competency development, relevant industrial relations. Schools are advised to improve the Link and Match 8+i partnership, optimize digital marketing, and innovate products using local resources.